The effects of feedback exercises on peak vertical Ground Reaction force and Rate of Loading associated with lower extremity injury in landing after volleyball blocks - Anis Rostami; Amir Letafatkar; Mehdi Khaleghi tazji (Sport Sciences and Health Research)
Female volleyball players are 2 to 10 times more likely than men to suffer from the injury of anterior cruciate ligament in motor patterns with decrease in repeated acceleration, landing, and rotation. The aim of the present study was to investigate the effect of 6 weeks of feedback exercises on thepeak vertical ground reaction force and rate of loading associated with lower extremity injury in landing after successful and unsuccessful defense in female university volleyball players. 32 female volleyball players (age range 18-24 years) were selected and randomly divided into feedback (n=16) and control (n=16) groups. The force plate was used to measure the peak vertical ground reaction force and the rate of loading in pretest and posttest. According to the findings, the significance levels were P=0.003 and 0.004 for the first and second peak of the VGRF in stick landing, P=0.005 and 0.012 in step-back landing, P=0.008 and 0.011 for the first and second ROL in stick landing, P=0.002 and 0.016 in the step-back landing. The results of this study showed that feedback exercises had positive effects on the prevention of injury in volleyball players through significant changes in the risk factors of anterior cruciate ligament injury. Therefore, it is suggested to use feedback exercises to reduce those risk factors associated with injuries of the anterior cruciate ligament and to have accurate retention and transfer of safe techniques during the exercise sessions to the competitions.